Cultural Heritage and Gamification: Xenia Progetti solutions that revolutionize the ways of learning and visiting cultural sites (Archeomatica, 2024)
In recent years, the concept of gamification has acquired increasing relevance, becoming a valid and recognized learningmethodology. Gamification, using characteristic elements of games, such as prizes, timed challenges and competitions,makes the learning process more engaging and interactive, thus promoting the acquisition of knowledge. When integratedwith technology, this method turns into a highly effective tool, also capable of improving the user experience,especially in certain contexts such as, for example, the cultural one. The adoption of gamification in cultural contexts not only attracts a larger and more diverse audience, but stimulates a more dynamic approach to culture and education.